Sweetening the transition in EU sugar preferences : the case of Fiji - Levantis, Theodore (2005)
Focuses on preferential access to EU sugar markets for ACP countries. Presents some background data on the ACP sugar preference scheme and it beneficiaries. Makes suggestions for diverting the funds spent on paying inflated prices for sugar into building a stronger social and economic base. Uses Fiji as a case study for testing quantitatively the implications of alternatives to trade schemes.